Genome-wide insights into the evolutionary history of conserved photosynthetic NDH-1 in cyanobacteria - Pang, Xiaoqin; Jiang, Yuanyuan; Yu, Jie; Ran, Zhaoxing; Ma, Weimin (Frontiers in Plant Science, 2025)
The integration of novel components into functional multi-subunit protein complexes is a key evolutionary strategy for enhancing stability, activity, and adaptation to oxidative stress. This is exemplified by the evolution of the conserved photosynthetic NDH-1 (cpNDH-1) complex, though its precise evolutionary history remains unresolved. In this study, we constructed a time-calibrated phylogenetic tree of cyanobacteria to trace the evolutionary trajectory of cpNDH-1. By mapping the orthologous of oxygenic photosynthesis-specific (OPS) subunits onto this tree, we found that the cpNDH-1 complex progressively acquired OPS subunits. Specifically, during the transition from non-photosynthetic to thylakoid-less photosynthetic cyanobacteria, cpNDH-1 incorporated OPS subunits NdhM, NdhN, NdhO, NdhP, and NdhS. Subsequently, NdhL, NdhQ, and NdhV were added as thylakoid-bearing photosynthetic cyanobacteria evolved. Our analysis reveals that the emergence of oxygenic photosynthesis was closely linked with the progressive incorporation of OPS subunits into cpNDH-1. We propose a two-step model for the evolution of these subunits, identifying potential driving factors behind this process. Genome-wide sequence analysis and structural predications further suggest that the OPS cpNDH-1 genes either evolved de novo or arose from modifications of existing genes. Collectively, these findings provide a robust framework for understanding the evolutionary emergence of OPS subunits in cyanobacterial cpNDH-1, underscoring the acquisition of new subunits as a critical adaptation to oxidative environments during the evolution of oxygenic photosynthesis.